The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.biochem.6b00061
|View full text |Cite
|
Sign up to set email alerts
|

Stopped-Flow Studies of the Reduction of the Copper Centers Suggest a Bifurcated Electron Transfer Pathway in Peptidylglycine Monooxygenase

Abstract: PHM is a dicopper enzyme that plays a vital role in the amidation of glycine extended pro-peptides. One of the crucial aspects of its chemistry is the transfer of two electrons from an electron-storing and transferring site (CuH) to the oxygen binding site and catalytic center (CuM) over a distance of 11 Å during one catalytic turnover event. Here we present our studies on the first electron transfer step (reductive phase) in the WT PHM as well as its variants. Stopped-flow was used to record the reduction kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Notably, copper ions are commonly found as the active sites in natural enzymes, such as laccase and amine oxidases. In this context, excellent works by Lu and co‐workers showed that copper is the element of choice for the design and synthesis of enzymes; however, the skeleton of these modified Cu‐containing enzymes still consists of proteins or amino acids. Thus, the development of new artificial protein‐like ligands containing anchored copper ions to mimic the activity of native enzymes is of great interest.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Notably, copper ions are commonly found as the active sites in natural enzymes, such as laccase and amine oxidases. In this context, excellent works by Lu and co‐workers showed that copper is the element of choice for the design and synthesis of enzymes; however, the skeleton of these modified Cu‐containing enzymes still consists of proteins or amino acids. Thus, the development of new artificial protein‐like ligands containing anchored copper ions to mimic the activity of native enzymes is of great interest.…”
Section: Introductionmentioning
confidence: 80%
“…In this context,e xcellent works by Lu [20][21][22][23] and co-workerss howed that copperi st he element of choice for the design and synthesis of enzymes; however,t he skeleton of these modified Cu-containing enzymes still consists of proteins or amino acids. In this context,e xcellent works by Lu [20][21][22][23] and co-workerss howed that copperi st he element of choice for the design and synthesis of enzymes; however,t he skeleton of these modified Cu-containing enzymes still consists of proteins or amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The data were fit by non-linear regression to a rate equation which describes the process as a combination of fast and slow pseudo first order reactions and is identical to that used previously to analyze the DMPD reduction of the WT PHM. 81 A t = A 0 + A 1 1 − e −k 1…”
Section: Reduction By Nn'-dimethyl Phenylenediamine (Dmpd)mentioning
confidence: 99%
“…The structures of the PHM and PAL domains of rat PAM, alone and in complexes with substrates, inhibitors, and other ligands, have been determined 11 15 . Other techniques used to study PHM have ranged from kinetics and kinetic isotope effect measurements 16 20 , to inhibitor design 21 – 24 , spectroscopy 25 29 including X-ray absorption spectroscopy (XAS) 17 , 30 33 , and computational studies 11 , 34 36 . These studies have provided significant insights into the mechanism of both domains, especially of PHM.…”
Section: Introductionmentioning
confidence: 99%